ANALISIS DETERMINAN TINGKAT KEPATUHAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI - Yuliani, Nur Laila (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2016)
This study is aimed at examining the effect of consciousness, quality of service,sanction, justice and education level of taxpayers to meet the compliance in the District and City of Magelang. The main background conducting this study is motivated by empirical studies on adherence to pay taxes which is still diverse and growing importance of revenues from taxes that the government expected. This study implemented the theory of planned behavior as a grand theory. The research sample consisted of 308 individual taxpayers who performs in the District and City of Magelang. This study provides evidence that the justice and positive infl uence on the educational level of compliance to pay taxes. The awareness, quality of service, and sanctions do not affect the compliance of paying taxes.